The Molecular Identification of Bacteria in Plastic Waste at the Pasir Bajing Garut Landfill : plastic waste - Tati Kristianti; Rifaatul Muthmainnah; Friska Junita; Iis Aisyah (UNIVERSITAS PGRI MADIUN, 2026)
Plastic waste remains a major environmental concern worldwide. Approximately 418,262 tons of plastic waste, accounting for 20% of the total waste accumulation, are deposited annually at the Pasir Bajing Landfill (TPA) in Garut, Indonesia. Under these conditions, plastic serves both as a selective substrate for certain microorganisms and as a potential carbon source. This study aimed to identify bacteria associated with plastic waste at the Pasir Bajing Landfill using molecular techniques. Polystyrene waste samples were collected from three different sampling sites within the landfill area. Phylogenetic analysis based on 16S rRNA gene sequences revealed three bacterial isolates: isolate 2 was identified as Acinetobacter baumannii, isolate 5 as Atlantibacter hermannii, and isolate 6 as a member of the family Enterobacteriaceae. These isolates belong to the phylum Proteobacteria and may possess the potential to degrade plastic materials. Further studies are required to evaluate their plastic-degrading capabilities and to elucidate the metabolic pathways involved in the biodegradation process.